Optimizing Software-Defined Networks with Fuzzy Logic-Based Enhancement of Openflow Protocol - Hasan Sajjad H. (BIO Web of Conferences, 2024)
Today, humans have a strong need to control their devices from a distance so that they can control the world more than before and explore it for various purposes such as how the universe came into being, discovering the way of creation, observing the events in Global situation and so on. Communication with remote devices can be possible in various ways. SDN networks provide a possibility to exchange information between heterogeneous nodes. Considering that in SDN networks, the nodes are very expensive and these nodes themselves are performing many tasks and various vital tasks; Therefore, the cost of each byte of memory occupied on these nodes is very expensive and must be managed in such a way that they have the highest efficiency. Therefore, to solve this problem, it is very necessary and costly to carry out large projects. In the proposed method of this research, by improving the OpenFlow protocol in software-based networks, it is tried to avoid the cooperation of nodes in the directional distribution (not dissemination) of a small data, from the accumulation of extra information in the nodes' memories. Finally, after the simulation, it was observed that the improvement rate of the proposed method has improved by 0.38%, 0.05%, and 0.04%, respectively, compared to RD, FLCFP, and LEACH2013 methods. The improvement rate of the proposed method compared to RD, FLCFP, and LEACH2013 methods was 0.65%, 0.059%, and 0.331%, respectively.